Early Childhood Self Regulated Learning Based on Javanese Local Wisdom Jawa - Titik Mutiah; Sulistyo Budiarto; Victor.A Pogadev (Indigenous: Jurnal Ilmiah Psikologi, 2024)
Abstract. The study describes early childhood self-regulated learning (SRL) based on the Javanese philosophy in Ki Hadjar Dewantara (KHD) & Ki Ageng Suryamentaram (KAS) concepts. This used a phenomenological qualitative approach on 6 subjects (3-5 years old) dyadic with their mothers in Yogyakarta. The main data were collected through interviews, participant observation, and supported by data of the children’s developmental maturity by filling out the Temperament Assessment Scale, Child's behavior and SDIDTK checklists. Data analysis techniques were carried out by organizing data, grouping based on themes and answer patterns, testing existing assumptions or problems with the data, writing research results. The results showed that the SRL in line with the process of ‘Free Spirit’ of the 6 subjects varied and contained dynamic abilities in their process. The environment (parents/family) had not consistently implemented SRL in their ‘Among’ (Asah Asih Asuh & Ing Ngarsa Sung Tulada) and Kawruh Pamamong (Ngulawantah-lare/regulating children) systems. The ability of SRL subjects to understand (Ngerti Sumerep), to feel (Ngrasa Sih) and to action (Nglakoni Nrimo) still had no clear pattern on subjects. The internalization of SRL was in the process of co-regulatory behavior.